Core training to reduce the performance gap between abled and disabled athletes in the canoe discipline - Taleb, M.; Alberti, S.; D'Isanto, T. (Journal of Human Sport & Exercise, 2021)
Paracanoe is a sport similar to the Olympic one in terms of rules and equipment, albeit with some differences. The problem concerns the performance gap between able-bodied athletes and the performance of KL3 athletes, attributable to the difficulty in controlling the trunk of the latter due to the weak contact between the lower limbs and the platform. The goal is to verify if, by carrying out core training sessions that aim to improve the stability, power and strength of the trunk in KL3 athletes, it is possible to reduce the performance gap between the two categories of athletes. The champion is made up of 16 athletes who have participatedin regional canoe and Paracanoe competitions: champion A is made up of 8 non-disabled male athletes aged 23 to 25, while champion B is made up of 8 male athletes, between 23 and 25 years, with functional classification KL3. Both groups performed the 200m flat-water canoe sprint race before and after 6 weeks, during which time group B performed core-training exercises 3 times a week. The independent sample T test was used as a statistical tool. The result is statistically significant (p < .05) at entry, while after 6 weeks of training, the result is not statistically significant (p > .05). With the use of stabilizing guesswork and core training, it is possible to narrow the gap and encourage sports inclusion.